Improving the supply chain of motor pumps to accelerate mechanized small-scale private irrigation in Zambia - Colenbrander, W.; van Koppen, Barbara (2023)
During the past decade, smallholder groundwater irrigation with motor pumps has increased considerably in Zambia. This study analyzes an important but hitherto ignored factor for adoption: the supply chain of imported motor pumps. The main obstacles for farmers are identified as: the highly centralized supply chain and financing facilities in urban hubs; lack of information about prices, which vary significantly for the same make and model of pump; lack of information and training on proper use and maintenance; and lack of financing facilities. The Zambia National Farmers Union seems best placed to remove these obstacles.